Serum Procalcitonin, Use of Antibiotics, and Patient Outcome - Bryan Tolentino, Robert C Goldszer, Alexandra Franco; Cynthia Rivera, Denise Diaz, Pooja Pundhir; Larissa Cabarga, Claudio Tuda, Kenneth Ratzan; Cubbedu, Luigi; Lydia Howard, Diana Morlote, Nancimae Miller (International Journal of Innovative Research in Medical Science, 2016)
Objective: To evaluate the impact of serum procalcitonin (PCT) testing on use of antibiotics and patient outcome. Design: A retrospective chart review evaluation of the patients who had a serum procalcitonin test performed at one medical center. Setting: One academic medical center, Mount Sinai Medical Center, Miami Beach. Participants: One hundred and forty four consecutive patients who had procalcitonin determined beginning in January 2014. Measurements: We analyzed patient age, mortality, length of stay in intensive care unit and total hospital stay, presence of positive blood culture, and if on antibiotics at forty- eight and one hundred and twenty hours after PCT determination. Results: There were seventy two patients with a positive PCT determination (>0.5 ng/ml) and seventy two patients with negative PCT (<0.5 ng/ml). Patients with a positive serum PCT had a longer hospital length of stay, longer length of stay in Intensive Care Unit (ICU), were more likely to have a positive blood culture, more likely to be on antibiotics at 120 hours after PCT, and had higher mortality, (p<.05). Conclusion: Serum PCT level appears to predict severity of illness, mortality, and continued use of antibiotics. Negative PCT did not predict stopping of antibiotic treatment at forty-eight hours after the test.